The concept of Fatwa (Islamic verdict) in Malaysia and the constitutional dilemma: a legislation or legal opinion? - Ansari, Abdul Haseeb; Arifin, Mahamad; Abdullah, Mohamad Asmadi; Chiroma, Magaji (2014)
In Malaysia, fatwa has been considered as a religious verdict that assists in regulating Muslim’s conduct of activities in the country. The Federal constitution of Malaysia has vested the responsibility for enacting laws in the hands of the Parliament at the Federal level and in the state Assemblies at the state level. On the other lane, the Administration of Islamic Law enactments of various states and Federal Territories in Malaysia have provided for the establishment of fatwa institutions in order to issue a binding fatwa and to regulate Islamic verdicts in various states in the country. This process of issuing legal verdicts has been drawing the attention of some people as to its constitutionality. Thus, it has been perceived as usurpation of the legislative powers of the Parliament and state Assemblies as enshrined in the Malaysian Federal Constitution. In reaction to the above, the paper attempts to examine the role and legal status of fatwa within the context of the Malaysian laws with a view to clarifying its legal position.